Brüche und Kontinuitäten: Die drei Vorgängerinnen der Gesellschaft für Musikforschung - Keym, Stefan (Die Musikforschung, 2023)
The article discusses features of (dis-)continuity between the three German musicological societies which existed before the foundation of the current “Gesellschaft für Musikforschung” (GfM). When the GfM was founded by Friedrich Blume in 1946/1947, it adopted the name of the first German-language musi- cological society: Robert Eitner’s “Gesellschaft für Musikforschung” (1868–1905). However, it has much more in common with its later predecessors: the “Internationale Musikgesellschaft” (1899–1914) and the “Deutsche Musikgesellschaft” (1918–1939). These societies established precedents for the structure of musicological societies, their congresses and journals. Even the close cooperation with a music publisher was continued by the new GfM, although Blume changed the partner from Breitkopf & Härtel to Bärenreiter. Furthermore, all three societies faced similar challenges: the relationship between musicological research and musical life, the tension between nationalist agendas and international cooperation, and the fluctuating forms of organization, which were easily destabilised in times of political turmoil.